Evaluation of motor fluctuations in Parkinson’s disease: electronic vs. conventional paper diaries - Asai, Kanako; Kawahara, Sayo; Shirahata, Emi; Iwasaki, Kimihiro; Nakai, Hikoichiro; Kajiyama, Yuta; Taniguchi, Seira; Ge, Lindun; Kakuda, Keita; Kimura, Yasuyoshi; Miyahara, Tadashi; Ueda, Hiroki R.; et al. (Frontiers in Neurology, 2024)
BackgroundPaper symptom diaries are a common tool for assessing motor fluctuations in Parkinson’s disease (PD) patients, but there are concerns about inaccuracies in the assessment of motor fluctuation due to recall bias and poor compliance. We, therefore, developed an electronic diary with reminder and real-time recording functions.Objectives and methodsTo evaluate the effectiveness of the electronic diary, we compared compliance and motor fluctuation assessment with a paper diary. Nineteen PD patients were recruited and recorded paper diaries every 30 min from 8 am to 8 pm for 7 days, followed by 7 days of electronic diary recording using a smartphone and smartwatch. Prior to the recording period, the Parkinson’s Disease Questionnaire (PDQ)-39 and the Movement Disorders Society-sponsored Unified Parkinson’s Disease Rating Scale-Revised (MDS-UPDRS) 1, 2, 3, 4 were measured. Patients completed a patient questionnaire on the usability of the diaries after the recording period.ResultsTotal reported time was significantly longer in paper diaries, but there was no significant difference in the number of entries (paper 115 [71–147] vs. electronic 109 [93–116], p = 0.77). There was a significant correlation between paper and electronic diaries with respect to motor status. ON time rate recorded in the electronic diary was significantly correlated with PDQ-39, MDS-UPDRS 1, 2, and 4, while MDS-UPDRS 1 was only correlated with ON time rate in the paper diary. The usability of our electronic diary was found to be satisfactory based on the results of patient questionnaire.ConclusionElectronic diaries are useful tools that more accurately reflect PD motor fluctuations.